Community Participation in Sanitation Programmes at Ashaiman - Addo, K.N. (University of Ghana, 2004)
The study was set to find out community participation o f sanitation programmes at Ashaiman. A sample o f 98 community members were selected through systematic random sampling technique from three out o f eleven electoral areas and questionnaires were administered to five and officials from TMA sub-zonal office at Ashaiman. The major findings were that: 1. Most o f the respondents were youth below 30 years who were mostly single. 2. The youth in the communities were not involved in any decision-making in terms of planning o f sanitation programmes. 3. Structures had not been put in place to facilitate community participation in sanitation activities. 4. There were a lot challenges in terms o f how to mobilize members o f the community for communal labour. 5. Absence o f number o f Non-Governmental organizations and other civil society in organization of sanitation programmes. The study concluded that in most communities in Ashaiman, there were no defined ongoing sanitation programmes. Finally, it is recommended community members and civil society organization should be mobilized to participate in sanitation programmes at Ashaiman while sanitary sites in the hands of private individuals must have permanent structures to establish small recycling plants to recycle waste dumped in the sites.
Thesis (Mphil)
Keywords: Sanitation; Communal Labour; Sanitation Sites; Recycle Waste; Sanitary Sites; Recycling Plants; Dumping Sites